Hypoxia in murine atherosclerotic plaques and its adverse effects on macrophages - Parathath, Saj (2013)
Hypoxia has been found in the atherosclerotic plaques of larger mammals, including humans. Whether hypoxia occurs in the plaques of standard mouse models with atherosclerosis has been controversial, given their small size. In this review, we summarize the findings of a recent report demonstrating that direct evidence of hypoxia can indeed be found in the plaques of mice deficient in apolipoprotein E (apoE−/−mice). Furthermore, studies in vitro showed that hypoxia promoted lipid synthesis and reduced cholesterol efflux through the ABCA1 pathway, and that the transcription factor HIF-1α mediated many, but not all, of the effects. These results are discussed in the context of the literature and clinical practice.